PENGEMBANGAN MEDIA POP UP BOOK CERITA RAKYAT DIPADU GAMES EDUKASI (POBCER-GE) UNTUK MENINGKATKAN SIKAP TOLERANSI SISWA KELAS II SEKOLAH DASAR - Adzimatnur Muslihasari; Nuraini (Didaktik : Jurnal Ilmiah PGSD STKIP Subang, 2025)
This study was motivated by the low level of tolerance among second-gradestudents at SD Negeri 02 Tlogorejo, which is attributed to the lack of adequatelearning facilities and infrastructure. The main goal of the research is to determinethe validity and feasibility of the POBCER-GE media (a Pop-Up Book of Folk Talesintegrated with Educational Games) in delivering tolerance-related content, as wellas to evaluate its effectiveness in improving students’ tolerance attitudes. Theresearch adopts a quantitative approach and follows the ADDIE developmentmodel, which consists of five phases: Analysis, Design, Development,Implementation, and Evaluation. The participants in this study were 15 second-grade students from SD Negeri 02 Tlogorejo, located in the Pagak District. Datacollection methods included observation, interviews, questionnaires, anddocumentation. Validation results indicated that media experts rated the POBCER-GE media at 98.33% (very valid), material experts at 88.33% (valid), andpractitioners at 93.33% (very feasible). Student trials revealed that the small groupachieved a validity percentage of 89.58%, while the large group scored 86.83%(very valid). Improvements in students’ tolerance attitudes were measured usingpretest and posttest questionnaires, yielding an N-Gain score of 0.73, which fallsinto the high category. Based on these findings, it can be concluded that thePOBCER-GE media is both valid and feasible, making it an effective educationaltool for enhancing tolerance among second-grade elementary students.